The cooling of the gravels used in the production of concrete by transpiration cooling method - Samsa, Neyran (My University, 2011)
BETON ÜRETİMİNDE KULLANILAN ÇAKILLARIN TERLEMEYLE SOĞUMA YÖNTEMİYLE SOĞUTULMASI Beton günümüzde ve çağlar boyunca her zaman büyük miktarda tüketilen bir yapı malzemesi olmuştur. Dünya nüfusunun ve yaşam kalitesinin artışının getirileri olan kentsel altyapı, ulaşım ve enerji gereksinimleri arttıkça teknolojide de ilerlemeler kaydedilmiş ve beton üzerine pek çok bilimsel çalışma yapılmıştır. Beton, kullanım amacına hizmet eden pek çok fiziksel özelliği içerdiği çimentonun suyla olan kimyasal reaksiyonu olan hidratasyon reaksiyonları ile elde eder. Gerek prizlenme sürecinde kullanımı nedeniyle, gerekse hidratasyon reaksiyonları sonucu açığa çıkan ısıdan dolayı betonun içerdiği su buharlaşır ve betonun hacminin azalmasına neden olur. Bunun sonucunda beton büzülür ve betonda çatlaklar oluşur. Baraj, köprü, yol yapımı gibi betonun fazla kullanıldığı yapılara kütle beton denir. Bu tür yapılarda, daha fazla beton ve su kullanıldığı için, normal yapılara göre daha fazla ısı çıkışı gerçekleşir ve dolayısıyla yüzeyde çatlakların oluşması daha ciddi bir önem taşır. Günümüzde kütle betonları için belirlenmiş olan ön soğutma işlemleri, betonun dökülmesinden sonraki kür işlemleri ve dökülme sonrasında yapılan soğutma işlemleri uluslar arası standartlara sahiptir. Yeni metotlar üstünde çalışmalar sürdürülmektedir. Bu çalışmada betonda çatlak oluşumunun engellenmesi amacıyla, betonun karışımında yer alan çakılların ön soğutma işleminden geçirilmesi hedeflenmiştir. Mevcut ön soğutma işlemlerine bir alternatif metot olarak soğutucu akışkan olarak hava kullanılmıştır. Çakılların yüzeyiyle temas eden hava akımı ile çakılların içindeki suyun buharlaşması ve buharlaşması için gerekli enerjinin çakıllardan sağlanması ile çakılların sıcaklığının düşmesi bu çalışmanın temelini oluşturmaktadır. Bu çalışmada genel olarak izlenen yöntem, yapılan deneyler ile veri elde edilmesi, deney düzeneğinin temel mühendislik yaklaşımı ile üstünde değişiklikler yapılması ve deney sonuçlarının tekrar görüntülenmesi; bunu takiben ısı transferinin temel prensipleri ile matematik modelinin oluşturulması, modelin analiz edilmesi ve deneylerden elde edilen verilerle modelin uyumluluğun karşılaştırılması şeklinde olmuştur.

THE COOLING OF THE GRAVELS USED IN THE PRODUCTION OF CONCRETE BY TRANSPIRATION COOLING METHOD Concrete has been the most widely consumed construction material during centuries. In the 21st Century, it is still the most consumed material. As a result of the increase in world’s population and the life standards moved up in the world, urban infrastructure, transportation and energy needs increased. Therefore, improvements in the science and technology have been accomplished and many scientific studies have been done on concrete. Concrete gains the most of its physical properties which serve the purpose of its use as a result of chemical reactions, called hydration reaction. Hydration is an exothermic reaction and heat is evolved during the setting of the concrete which is called heat of hydration. As the hydrolysis reactions occur in the fresh concrete, some part of water is used for hydration reaction and some part evaporates due to the temperature increase. Water loss at the fresh concrete causes decrease in volume and crack formation occurs. In some constructions like dams, bridges and pavements, concrete is used in large quantity. The concrete, in such constructions is called “mass concrete”. In these constructions, since more concrete and water is used, more heat is generated and it causes cracks on the surface which is a serious problem. Nowadays, pre-cooling, curing and post-cooling methods are currently applied methods in different steps of concrete production and setting of the production. They have already been standardized by international publications. Also, studies on alternative methods are currently done. In this study, the mail goal is to cool the gravels prior to mixing with other ingredients of concrete to prevent crack formation in the concrete. Air is used as the coolant fluid as an alternative to the current pre-cooling methods. As the air flow contacts with the gravels’ surface, the evaporation of the water in the gravel content is achieved. The energy which is needed for the evaporation is absorbed from the gravels and this leads to the cooling of the gravels. In this study, firstly experiments were done and the data was reviewed to decide if the results corresponded to the logic of the study and to improve the experimental set up if it is necessary. A mathematical model was generated using the main principles of heat transfer, it was analyzed, improved and the compliance of the model with the experimental results was compared.
Keywords: Kimya